EKONOMI, ORANG TUA DAN PENDIDIKAN TINGGI (STUDI PADA PETANI SIWALAN MASYARAKAT DESA PRAGAAN DAYA PRAGAAN SUMENEP) - Mujibno Mujibno (Assyarikah: Journal of Islamic Economic Business, 2020)
The economic status of parents has an important role in influencing children's education. Higher education for children is very urgent, especially in responding to the challenges of this era. As a parent, there is not much that can be done except by providing the best education.The purpose of this study is to identify and describe. First, how is the perception of the palm farmers towards the higher education of their children in Batu Jaran Hamlet, Pragaan Daya Village, Pragaan Sub-District. Second, what factors motivate parents to continue their children's education to college? This study uses a qualitative field research approach, while the methods used are observation, interviews and documentation methods.As for the results of this study, it can be concluded that the perception of palm farmers towards their children's higher education still assumes that the cost of higher education for their children is still expensive while their average income is low. so that the palm farmers, must really take into account the income and expenditure. This is done so that their children can still go to school to the highest level of education.